AFFIXATION OF BUGINESS PATTINJO DIALECT IN BENTENG PINRANG - SUNUBI, ABDUL HARIS (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2015)
The aim of this reserch is to discuss the affxation of vernacular Indonesia as general lay and specially the vernacullar of Benteng Pinrang society. In Benteng Pinrang use Buginess language pattinjo dialect. This dialect is different with other because this dialect is combination of Enrekang Language and Buginess Pinrang dialect. It is called assimilation. This research used descriptive method which is mean to give description about the cause of Benteng society use Pattinjo dialect. In this research, the researcher use qualitative research as design of this research. Qualitative is the collection, analysis, and interpretation of comprehensive and visual (non numerical) data. Qualitative research is the collection analysis and interpretation of comprehensive. Source of data this research is the native speaker of pattinjo dialect who live in Benteng Pinrang Parepare. Based on observation of the researcher in Benteng Pinrang most the people used native language in communication and interaction with other people. The native language of Benteng society is Bugis language dialect pattinjo. Bugis Language dialect pattinjo happen because there is assimilation between Bugis language and Enrekang Language